Diversificação em áreas cultivadas com tabaco e a territorialização da indústria fumageira: o caso do cultivo de tabaco orgânico no município de Canoinhas/SC - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The transformations that occurred in the field resulting from the modernization of agriculture led to the artificialization of space and techniques influencing new organizations and territorial dynamics. The advancement and strengthening of the tobacco production chain under the domination of monopoly capital intensifies the specialization between sectors, making production integrated with industry. In the municipality of Canoinhas - SC, tobacco production is territorialized in family-based agriculture, implying this production both in mercantile interests and in the survival of families. But it must be considered that by the end of the 1990s, tobacco production started being criticized, and restrictive measures of production and consumption began to be elaborated. The Framework Convention on Tobacco Control is the first health treaty regarding tobacco and proposes the introduction of economically capable alternatives to generate income for farmers. The reaction of the tobacco industry in the face of criticism is to adopt measures to strengthen and valorize production, supported by this scenario, companies use organic tobacco in an attempt to minimize anti-tobacco criticism and at the same time to open new markets. In this sense, the main objective of this study was to highlight the current impasses of conventional tobacco production and the prospects of production diversification, based on the company initiatives in search of productive alternatives that maintain their active market with organic tobacco. For this analysis, bibliographical research and data collection were carried out through semi-structured interviews with public and private agents and farmers who are related to tobacco. Through extensive exploratory bibliographical research, we analyze the transformations resulting from the actions against tobacco production evidenced in recent years and the conditioners of the diversification processes in areas with tobacco. As one of the elementary results of this dissertation we have dichotomous views on organic tobacco as a process of crop diversification, sometimes it is seen by those favoring production as a new production model based on sustainable molds, sometimes it is seen by those against the cultivation, as a way of minimizing the criticism, increasingly imposing to the sector.
Keywords: Diversificação; Empresas fumageiras; Tabaco orgânico; Territorialização; Diversification; Tobacco companies; Organic tobacco; Territorialization; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA